Public Perception of Mangrove Crab Catching Restrictions in Kuala Lupak Village, Tabunganen District, Barito Kuala Regency - Suhardi, Suhardi; Erma Agusliani; Irma Febrianty (Universitas Islam Lamongan, 2025)
Due to increasing pressure from exploitation, the government has issued several regulations to maintain the sustainability of mangrove crab resources. Regulation of the Minister of Maritime Affairs and Fisheries (Permen KKP) Number 17 of 2021, later amended by Regulation of the Minister of Maritime Affairs and Fisheries Number 16 of 2022, regulates the utilization of lobsters, crabs, and swimming crabs in Indonesian territory. The research aims to analyze public perceptions of restrictions on catching mangrove crabs in Kuala Lupak Village, Tabunganen District, Barito Kuala Regency. This research was conducted in Kuala Lupak Village, Tabunganen District, Barito Kuala Regency, South Kalimantan Province. The perceptions and behavior of fishermen towards the regulations of the Minister of Maritime Affairs and Fisheries, the entire population of mangrove crab fishermen will be the research respondents, namely 50 respondents. Data analysis used in this research activity is a Likert scale used to measure the attitudes, opinions, and perceptions of an individual or group of people about social phenomena. Fishermen's Perception of Regulation (Very Positive) Fishermen's perception of the Regulation of the Minister of Maritime Affairs and Fisheries Number 7 of 2024 is categorized as Very Positive (average score close to 4.00, on a scale of 1-4). Acceptance of Benefits: Fishermen strongly agree that this regulation is beneficial and effective in the long term, especially because the community has felt its impact directly, namely the size of the crabs caught tends to be larger (increasing the selling price). Understanding of Conservation: There is adequate understanding of the need for conservation, including the importance of keeping egg-laying crabs and crabs below the minimum size so that resources do not become extinct.